Animal salmonelloses: a brief review of “host adaptation and host specificity” of Salmonella spp. - Grammato Evangelopoulou; Spyridon Kritas; Alexander Govaris; Angeliki R. Burriel (Veterinary World, 2013)
Salmonella enterica, the most pathogenic species of the genusSalmonella, includes more than 2,500 serovars, many of which are of great veterinary and medical significance. The emergence of food-borne pathogens, such as Salmonella spp., has increased knowledge about the mechanisms helping microorganisms to persist and spread within new host populations. It has also increased information about the properties they acquire for adapting in the biological environment of a new host. Thedifferences observed between serovars in their host preference and clinical manifestations are referred to as “serovar-host specificity” or “serovar-host adaptation”. The genus Salmonella, highly adaptive to vertebrate hosts, has many pathogenic serovars showing host specificity. Serovar Salmonella Typhi, causing disease to man and higher primates, is a good example of host specificity. Thus, understanding the mechanisms that Salmonella serovars use to overcome animal species' barriers or adapt to new hosts is also important for understanding the origins of any other infectious diseases or the emergence of new pathogens. In addition, molecular methods used to study the virulence determinants of Salmonella serovars, could also be used to model ways of studying the virulence determinants used by bacteria in general, when causing disease to a specific animal species